Strain Distribution Measurement of a Shear Panel Damper Developed for Bridge Structure. (12th September 2013) - Liu, Y.; Aoki, T.; Shimoda, M.
Abstract : A shear panel damper using low-yield steel is considered as one of cost-effective solutions to reduce earthquake damage to building structure. In this paper, we describe the development of a shear panel damper with high deformation capacity, which is a necessary condition for it to be a bridge bearing. The development is based on the measurement of strain distribution of the shear panels under cyclic loading test. For the measurement, an image processing technique is proposed to use with the two-dimensional finite element method, in which a constant stress triangular element is employed. The accuracy of the measurement is validated by comparing with the results acquired by strain gauges. Various shapes of shear panels are tested in the experiment to obtain the relationship between the strain distribution and the deformation capacity. Based on the results of the experiment, the shear panel damper is improved to achieve high seismic performance with large deformation capacity.